Protección social transnacional en Centroamérica. Reflexiones a partir de tres contextos de movilidad - Sergio Salazar; Koen Voorend (Cahiers des Amériques Latines)
The article parts from the debates on transnational social protection to analyze cases of south-south migration in Central America and Mexico, of both labor mobility of Nicaraguans towards Costa Rica, and economic and social violence related mobility of people from Honduras and El Salvador to the USA. Studying the protection practices and resource environments that arise around the population in movement, brings an analytical and methodological contribution in the consideration on transnational social protection in southern contexts. The cases analyzed show that, in these conditions, protection practices fall mainly on individuals and family networks, as well as on the third sector and the market in conditions of informality.